“Sugar Crisis” in Russia during First World War (based on Materials of Eastern Siberia) - O. M. Dolidovich (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The reasons for the shortage and high cost of sugar in one of the rear Russian regions in the First World War are considered. The features of sugar production and trade in the Russian Empire, as well as the causes of “the sugar crisis” in the war period in the country and cities of Eastern Siberia are analyzed. It is shown that in the pre-revolutionary period there was a system of state-monopolistic regulation of the industry. Sugar excise is presented as one of the most important sources of replenishment of the state treasury: legislative retention of high prices in the domestic market provided fabulous profits to sugar producers. It is reported that during the war, sugar production and trade affected the following processes: the increase in excise duty in 1914 and 1916, the reduction in production against the background of a sharp increase in consumer demand from the population and the army, increased speculation. It is reported that the fight against the deficit was carried out through bureaucratic economic measures (introduction of tariffs and fixed prices, centralization of distribution, etc.), which were ineffective. Eastern Siberia is characterized as not having its own sugar production: the region depended on supplies from the European part of the country. The author concludes that the general disorganization of economic life and the disruption of railway communication led to a crisis of supply in the early period of the war. It is noted that a very limited arsenal of actions of local authorities (taxing prices, municipal purchases of sugar, the introduction of card distribution) could not affect the situation as a whole.